Pertanggungjawaban Pidana Terhadap Pelaku Penderita Shizophrenia Berdasarkan Kitab Undang- Undang Hukum Pidana. - ', Safrizal; ', Erdianto; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In reality, not all crimes are committed by someone who has a healthy mental state. A person who has a mental disorder also has a role in criminal acts. As the case of Rodrigo Gularte drug dealer where the alleged perpetrators are Schizophrenic sufferers. Rodrigo Gularte was sentenced to death in a Supreme Court ruling on the review of No.46 PK / Pid.Sus / 2010. In this case the decision is used as a measure of the extent to which the sufferer of schizophrenia to be asked for criminal responsibility. The purpose of this Thesis Writer is First, to know the criminal responsibility to the perpetrators of Schizophrenia patients based on the Criminal Code. Second, knowing the legal review of the imposition of capital punishment by a judge in the judgment of the Supreme Court Court on the review of No.46 PK / Pid.Sus / 2010 against Schizophrenia perpetrators based on the Criminal Code. Writing this research using the type of normative legal research, reviewing legislation that refers to the Criminal Code. This study has a descriptive nature. Sources The data used are secondary data consisting of primary and secondary legal materials. Techniques of collecting data on literature review method or document study such as books or prevailing laws and regulations. So this study has a relationship in the legislation and in the literature. From the results of research problems there are two main things that can be concluded. First, the criminal responsibility of the perpetrators of Shizophrenia sufferers based on the Criminal Code is included in the category of Article 44, then according to the provisions of criminal law can’t be punished, but the act of the person is still an act contrary to the law (Wederrechtelijk) but the perpetrator is given a forgiving excuse The law so that the perpetrator's (Schuld) errors are erased. Secondly, the legal review of the imposition of capital punishment by judges in the judgment of the Supreme Court Court of Judicial Review No.07 PK / Pid.Sus / 2010 against the Schizophrenic offender under the Criminal Code is not a judge's stance contrary to the principle of legality, based on the judge's conviction and court evidence that the defendant shows an attitude that can be held accountable for his crime.